Quality of care for frail older persons in a homecare setting: what is it and how can it be measured?. (2nd November 2017) - Cohen-Mansfield, Jiska; Sela, Adi Hannah; Iecovich, Esther; Golander, Hava
ABSTRACT: Background: As more older persons opt to age in place, there is a growing trend to hire migrant workers as live-in caregivers to care for them. This raises the need to examine the quality of care they receive within this unique care setting. The objective of this pilot study was to establish the components of quality of care as provided by migrant live-in caregivers. Methods: We interviewed a convenience sample of older persons cared for by migrant live-in caregivers and their relatives. When relatives reported that older persons could not be interviewed due to advanced dementia, only relatives were interviewed. Overall, 72 older persons and 117 relatives were interviewed. We used the Quality of Care Questionnaire (QuCQ) developed for this study to examine the main components of quality of care in this population. Results: Factor analysis using older persons' data revealed two factors. In the first factor, "caretaking, " items concerning provision of prompt care exhibited the highest loadings. Items measuring interpersonal aspects of the care dynamic had the highest loadings in the second factor, thus labeled "relationship." The factor analysis based on relatives' data yielded similarities and differences with the one based on older persons' data. Yet, there were significant correlations between relative and older persons' responses when using the older persons' factor structure. Conclusions: According to older persons and relatives, quality of care depends on the extent to which older persons' care-related needs, as well as social ones, are addressed. Appropriate evaluation of quality of care in the live-in setting is important for its improvement.